Proximate Analysis of Tempeh Nuggets with the Addition of Oyster Mushroom (Pleurotus ostreatus) - Siti Nurlani Harahap; Lily Novianty; Dewi Novina Sukapiring (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Basic human needs include nutritional needs. There are an increasing number of new and high-quality foods that perform optimally for human activities. Currently consumers prioritize food that is practical and easy to consume, one of which is nuggets. The popular nuggets is chicken nuggets which have a high fat content and cholesterol which is harmful for health. Currently there are developments of high-fiber nugget innovations through the optimization of tempeh and oyster mushrooms This study aims to analyze the proximate to determine the water content, protein content, carbohydrate content, fat content, and ash content in tempeh nuggets with the addition of oyster mushrooms. The method in this study uses an experimental method carried out in the laboratory by analyzing the water content, carbohydrate content, fat content, ash content, and protein content of the nuggets. Based on the research that has been conducted, the average results of the highest water content of tempeh nuggets combined with oyster mushrooms is in the S3 treatment (51.75%), protein content in the S3 treatment (13.747%), fat content in the S2 treatment (13.69%), ash content in the S1 treatment (6.057%) and carbohydrate content in the S1 treatment (27.113%)